GO Station & GO Mart / Nur Azirah Iryani Razali ... [et al.] - Razali, Nur Azirah Iryani; Azman, Siti Nur Zulaikha; Kamarrudin, Nuramalia; Afza Aini Zam, Azri Azim (2023)
Businesses are increasingly taking steps to halt the cycle of rising pollution and reduce the use of natural resources, which increases CO2 emissions in the environment. Malaysia is now riding the EV wave. Charging stations are soon becoming a big change in the business setting. In the next years, charging stations will increase and take over the worldwide market. To begin, G0 Station and G0 Mart define the services by providing a charging station on city streets for motorcycles, scooters, and other electric vehicles. With the proper location, excellent services, and effective marketing, the company may reliably serve a significant number of clients who own electric vehicles. It is critical to note that establishing an electric vehicle charging station company requires considerable investment cash, careful planning, and attention to detail in order to remain successful. G0 Station wishes to develop a business that is a fully registered and licensed. Electric Vehicle Charging station in a popular area in Klang Valley, Malaysia. The company will run a public quick-charge station with a 35 Kw rapid charging system. The stations, which will be located throughout key cities in Malaysia's Kuala Lumpur, would provide complete service. G0 Mart, a convenience shop, would be one of the services provided. Companies are open to using cutting-edge technologies in the electric car charging market. The company's great customer service and range of other supplementary services will position it as one of the most favoured electric car charging stations in Klang Valley, Malaysia. G0 Station and G0 Mart are dedicated to achieving excellence and financial success through unwavering service and honesty. The company is in the industry to establish a good name for itself. Furthermore, the company is convinced that the company's ideals and service quality will enable it take the electric car charging station business to enviable heights while also attracting the number of clients that will make the business very lucrative. G0 Station and G0 Mart will make certain that all customer receives first-rate service anytime they visit the electric car charging stations and convenience shop. In terms of business expertise, cash, time, and a rapid return on investment, starting a charging business is one of the most promising enterprises today. One of Malaysia's brightest future possibilities. The charging station has the potential to benefit the environment by lowering pollution and fuel consumption. As a consequence, creating charging stations improves the economy as well as the long-term viability of future trends.